Sheehan's syndrome: baseline characteristics and effect of 2 years of growth hormone replacement therapy in 91 patients in KIMS - Pfizer International Metabolic Database - Kelestimur, F; Jonsson, P; Molvalilar, S; Gomez, JM; Auernhammer, CJ; Colak, R; Goth, MI (Oxford Univ Press, 2005)
Objective: Sheehan's syndrome occurs as a result of ischaemic pituitary necrosis due to severe postpartum haemorrhage. It is one of the most important causes of hypopituitarism. and hence growth hormone deficiency (GHD), in developing countries. However, little is known about the effects of growth hormone (GH) replacement therapy in patients with Sheehan's syndrome. Design: The demographic background characteristics of 91 GH-deficient patients with Sheehan's syndrome (mean age +/- S.D., 46.34 +/- 9.4 years) were compared with those of a group of 156 GH-deficient women (mean age +/- S.D., 51.5 +/- 1-13.1. years) with a non-functional pituitary adenoma (NFPA). The baseline characteristics and the effects of 2 years of GH replacement therapy were also studied in the 91 patients with Sheehan's syndrome and an age-matched group of 100 women with NFPA (mean age +/- S.D. 44.5 +/- .0.2 years). Results: All patients were enrolled in KIMS (Pfizer International Metabolic Database). Patients with Sheehan's syndrome were significantly younger at pituitary disorder onset. diagnosis of GHD and at entry into KlMS than patients with NFPA (P < 0.01), and had significantly lower insulin-like growth factor I levels (P < 0.001). At baseline, quality of life (QoL) was significantly (P < 0.05) reduced in patients with Sheehan's syndrome compared with those with NFPA (P < 0.001). With regard to treatment effects, lean body mass increased significantly (P < 0.05), QoL improved significantly (P < 0.05) and total and low-density lipoprotein-cholesterol decreased significantly (P < 0.05) in patients with Sheehan's syndrome after 1 year of GH replacement therapy. Similar significant changes in QoL and lipid profiles occurred in patients with NFPA after 2 years of GH replacement. Blood pressure remained unchanged in patients with Sheehan's syndrome. but decreased significantly (P < 0.01) in the group with NFPA after 1 year, before returning to pretreatment levels at 2 years. Conclusions: In conclusion, patients with Sheehan's syndrome have more severe GHD compared with individuals with NFPA. GH replacement therapy in patients with Sheehan's syndrome may have beneficial effects on QoL. body composition and lipid profile.
Keywords: Gh Deficient Adults; Hypopituitary Adults; Premature Mortality; Dose Titration; Vasopressin; Life